2002
DOI: 10.1111/j.1651-2227.2002.tb01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between capillary and arterial lactate in the newborn

Abstract: Fauchère J-C, Bauschatz AS, Arlettaz R, Zimmermann-Bär U, Bucher HU. Agreement between capillary and arterial lactate in the newborn. Acta Paediatr 2002; 91: 78-81. Stockholm. ISSN 0803-5253Arterial blood lactate is a reliable indicator of tissue oxygen debt and is of value in expressing the degree and prognosis of circulatory failure as a result of various diseases. Therefore, the practical issue of whether capillary lactate measurements might be of equal value was investigated in newborns. In total, 193 simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…a Sampling times: 1 = before anesthesia (baseline); 2 = 1 hour after induction of anesthesia; 3 = end of surgery; 4 = after 1 hour in the recovery room; 5 = 4 hours after surgery. Some studies found no difference in the lactate levels sampled from the central vein, pulmonary artery or arterial site, in hemodynamically stable but critically ill patients [8][9][10][11]. Others found an arteriovenous lactate level discrepancy [12] or reported that lactate level may be higher in blood collected from the inferior vena cava [13].…”
Section: Discussionmentioning
confidence: 98%
“…a Sampling times: 1 = before anesthesia (baseline); 2 = 1 hour after induction of anesthesia; 3 = end of surgery; 4 = after 1 hour in the recovery room; 5 = 4 hours after surgery. Some studies found no difference in the lactate levels sampled from the central vein, pulmonary artery or arterial site, in hemodynamically stable but critically ill patients [8][9][10][11]. Others found an arteriovenous lactate level discrepancy [12] or reported that lactate level may be higher in blood collected from the inferior vena cava [13].…”
Section: Discussionmentioning
confidence: 98%
“…All blood gases obtained during the first 24 h of life were retrieved from patient's records, and a lactate value was available for each sample. This included arterial, capillary and venous samples [6,13,16].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there is no consensus whether the sample should be drawn from the arterial, peripheral venous, or capillary blood. Most investigators found a satisfactory agreement comparing capillary or venous lactate levels with arterial levels (25)(26)(27)(28). In our opinion, such sampling should therefore be encouraged as patient undergoes this procedure with a minimal risk and inconvenience.…”
Section: Discussionmentioning
confidence: 99%
“…Blood lactate levels are frequently measured, usually to detect tissue hypoxia (24)(25)(26)(27). However, the blood lactate monitoring in critically ill patient remains controversial considering the risk assessment.…”
Section: Discussionmentioning
confidence: 99%